Improving Expressive Language Skills Using Characterized Hand Puppets - Ristiyani , Dwi; Mulyono, Rahmat (research, training and philanthropy institution Natural Aceh, 2023)
There are four language skills, namely, listening, speaking, reading, and writing. Kindergarten-aged children only need to hear and speak correctly and according to their age development. According to Departemen Pendidikan Nasional (2003), the fiction of language development for early childhood is as a means of communication with the environment, as a tool for developing children's innate, actual abilities, as a tool for developing children's expression, and as a tool for expressing feelings and thoughts to others. This study aimed to improve early childhood expressive language skills using character hand puppets in group B1 TK ABA Wonosari IV as many as 15 children. Data collection through observation and documentation. The results showed an increase in indicators in the pre-cycle conditions of 13% and 60% in the first and 93% in the second cycles. The power analysis results concluded that using character hand puppet media could improve expressive language in group B1 TK ABA Wonosari IV. The researcher suggests that teachers use character puppet media to improve children's expressive language skills.